Implementasi Sistem Pengendalian Manajemen, Komitmen Organisasi, Dan Akuntansi Pertanggungjawaban Terhadap Kinerja Manajerial : Case Study Wisata Gentong Mas Kecamatan Wajak Kabupaten Malang - Agus Wiastono; Wiwit Setyo Wardani; Indah Datin Nadliroh; Ferra Eka Ramadhani (JOURNAL INNOVATION AND COMMUNITY SERVICE, 2022)
This research was conducted to examine and analyze the influence of the implementation of accountability accounting, organizational commitment, and management control systems on managerial performance at the Malang Tourism Office. This type of research is quantitative. This research uses a questionnaire for data collection. The population in this research were all employees who worked at the Malang Tourism Office. The number of samples in this research was 32 employees. The sampling technique used is simple random sampling technique. The data analysis used in this study is Multiple Linear Regression which is processed with SPSS software version 21. The results of the research indicate that the implementation of accountability accounting has a positive and significant influence on managerial performance. Organizational commitment has no influence on managerial performance. Managerial performance is not based on a strong commitment as a motivation to improve individual and organizational performance.